2022
DOI: 10.3390/app12042067
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Electromagnetic Induction and Electrical Resistivity Tomography for Digital Monitoring and Assessment of the Soil: A Case Study of Al-Ahsa Oasis, Saudi Arabia

Abstract: Al-Ahsa Oasis is one of the main and oldest agricultural centers in Saudi Arabia and one of the largest natural oases in the world. It is the largest irrigated agricultural oasis worldwide. The cultivated area is about 12,000 hectares in the region of Al-Ahsa. Groundwater was considered the main water source, if not the only source, for the different purposes of Al-Ahsa Oasis. However, due to groundwater depletion from these aquifers, treated wastewater is currently used to meet the shortage of irrigation wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The soil sample displayed relatively high electrical conductivity (10 dS m −1 ), demonstrating the slight salinity of the soil under consideration. Various reasons could explain soil salinity, including poor rainfall that deposits salt on the soil surface [27]. Moreover, Nawar et al (2014) have also reported the salinity in the soils of Al-Ahsa (8-16 dS m −1 ) [28].…”
Section: Discussionmentioning
confidence: 97%
“…The soil sample displayed relatively high electrical conductivity (10 dS m −1 ), demonstrating the slight salinity of the soil under consideration. Various reasons could explain soil salinity, including poor rainfall that deposits salt on the soil surface [27]. Moreover, Nawar et al (2014) have also reported the salinity in the soils of Al-Ahsa (8-16 dS m −1 ) [28].…”
Section: Discussionmentioning
confidence: 97%
“…It is known for being one of the largest date palm (Phoenix dactylifera, Arecales: Arecaceae) producers in the world. The crops thrive on salty soils that are fed from an underground aquifer and irrigated by the flow of many artesian springs, which allows agriculture all year round in a region that is otherwise a sandy desert (Mohammed et al 2022).…”
Section: Collecting Site and Rearingmentioning
confidence: 99%
“…It is considered the world's largest and most important oasis, covering 320 km 2 at about 150 m above sea level and containing numerous date palm and crop farms that play a vital role in economic development. 2 Al-Asfar Lake, a vast man-made lake, was extensively eutrophied by Al Ahsa clay farm and animal waste and treated and untreated sewage water from a 1971 water network system. 3 The lake is characterized by a massive expanse of open water and extensive growth of flora much appears around the lake.…”
Section: Introductionmentioning
confidence: 99%